Bacterial Life and Dinitrogen Fixation at a Gypsum Rock - Boison, Gudrun (American Society for Microbiology, 2004)
The organisms of a bluish-green layer beneath the shards of a gypsum rock were characterized by molecular techniques. The cyanobacterial consortium consisted almost exclusively of Chroococcidiopsis spp. The organisms of the shards expressed nitrogenase activity (C(2)H(2) reduction) aerobically and in light. After a prolonged period of drought at the rock, the cells were inactive, but they resumed nitrogenase activity 2 to 3 days after the addition of water. In a suspension culture of Chroococcidiopsis sp. strain PCC7203, C(2)H(2) reduction required microaerobic conditions and was strictly dependent on low light intensities. Sequencing of a segment of the nitrogenase reductase gene (nifH) indicated that Chroococcidiopsis possesses the alternative molybdenum nitrogenase 2, expressed in Anabaena variabilis only under reduced O(2) tensions, rather than the widespread, common molybdenum nitrogenase. The shards apparently provide microsites with reduced light intensities and reduced O(2) tension that allow N(2) fixation to proceed in the unicellular Chroococcidiopsis at the gypsum rock, unless the activity is due to minute amounts of other, very active cyanobacteria. Phylogenetic analysis of nifH sequences tends to suggest that molybdenum nitrogenase 2 is characteristic of those unicellular or filamentous, nonheterocystous cyanobacteria fixing N(2) under microaerobic conditions only.